Pendampingan Pengajuan Perizinan Berusaha NIB Badan Hukum Panti Asuhan Addinu Waddun’ya melalui Sistem OSS RBA - Arifin, Imam Zarkasyi; Yurenaudia, Azzahra; Ningtyas, Andriana Ayu; Nailufar, Syadzaya (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
This community service activity was carried out at the Addinu waddun`ya Orphanage Foundation (ADINDA) located in Surabaya, East Java. This activity focuses on business licensing assistance for foundations through the Online Single Submission Risk-Based Approach (OSS-RBA) system. The orphanage foundation is a legal entity engaged in the social sector so that it has the same rights and obligations as other legal entities including in terms of business licensing. This business licensing assistance is carried out through several stages, namely the preparation stage, the NIB introduction stage, and the implementation stage. The result of this activity is that the foundation successfully obtained a Business Identification Number (NIB) and other business licence documents. This activity is expected to provide benefits for the foundation in carrying out its business activities legally and sustainably.